PENERAPAN TEKNOLOGI DIGITAL MARKETING UNTUK MENDUKUNG PERTUMBUHAN UMKM DI SURABAYA - I Gusti Ayu Sri Deviyanti; Diofa Revalino; Sri Rahayu; Pram Eliyah Yuliana; Kelvin Kelvin; Suhatati Tjandra; Setya Ardhi; Endang Sriwahyuni (LPPM Universitas Islam Darul 'Ulum Lamongan, 2025)
This community service activity aims to improve the understanding and skills of MSME actors in Kelurahan Klampis, Surabaya, in implementing digital marketing as a marketing strategy to expand market reach and increase sales. The training includes an introduction to digital marketing, social media-based marketing strategies, and practical use of digital tools for creating promotional content. Additionally, intensive mentoring is conducted to ensure the successful implementation of digital marketing strategies. The evaluation results show that 90% of participants found the training useful, and 80% of participants successfully applied the strategies taught. Some participants reported a sales increase of up to 30% within two weeks after the training. Although there were some challenges, such as limited access to technology and technical skills, this training and mentoring successfully had a positive impact on the participants' business growth. Moving forward, continuous mentoring is needed to optimize the implementation of digital marketing in MSMEs.